Breakout [videorecording (DVD)] - Slagle, Brandon; Thompson, Robert, (Screenwriter); Mandylor, Louis; Andrews, Kristos; Krause, Brian, 1969-; Sizemore, Tom, 1961-2023 (Uncork'd Entertainment, 2022)
Having taken control of a maximum-security prison and recruited the other prisoners as his army, a criminal mastermind and former LAPD explosives expert faces off against a rogue hostage negotiator and a retired Black Ops agent who had been visiting his incarcerated son.